CONCEPTE PRIVIND CONTROLUL FINANCIAR - Caprian, Iulia (CEP USM, 2010)
This thesis is based on the conceptual approach to the notions related to the Court's essence of activity. Are analyzed the concepts of control, administrative, financial control, public financial control, performance audit - all these in order to determine their importance and need in the human activity. Also is individualized the public financial system in whose framework we determine the place of the Court of Accounts as state authority.
Keywords: controlul financiar; funcțiile controlulului financiar